ESG rating and stock returns during the Russia-Ukraine war : European evidence - Viitanen, Jonas (My University, 2024)
In this thesis, the impact of a responsible investment strategy on stock returns is studied in context of the escalation of the Russia-Ukraine war. This study is an event study aiming to investigate whether ESG ratings (Environmental, Social, Governance) of companies affected stock returns immediately after the escalation of the war. The war provides an interesting opportunity to explore the impact of responsibility on stock returns during an exceptional time. Based on previous research, conflicting assumptions can be made regarding the impact of ESG ratings on stock returns. Although various studies have reached different conclusions, it can generally be inferred that there is a relationship between stock returns and corporate responsibility. The thesis examines European stocks belonging to the STOXX Euro 600 index. It reviews existing literature on responsible investing and the impact of crises on stock returns. Additionally, the thesis includes an empirical section where the topic is analyzed using statistical methods. Various OLS regressions are employed in the empirical analysis to determine the effect of ESG ratings on stock returns in the context of the Russia-Ukraine war escalation. The results suggest that there is no statistically significant relationship between ESG ratings and stock returns when considering the overall ESG rating. However, when examining the E, S, and G components of corporate responsibility separately, a slight impact on stock returns related to social, environmental, and governance responsibility can be observed. Social and environmental responsibility show a positive correlation with stock returns, while governance responsibility exhibits a negative correlation. As a side note, the study also investigates the impact of NATO membership on stock returns during the escalation of the war. The results suggest that NATO membership did not significantly affect stock returns.

Tässä tutkielmassa tarkastellaan vastuullista sijoitusstrategiaa ja osaketuottoja Venäjän ja Ukrainan välisen sodan alkaessa. Kyseessä on tapaustutkimus, jonka tavoitteena on selvittää, vaikuttaako yritysten ESG-luokitus (Environmental, Social, Governance) osakkeiden tarjoamaan tuottoon välittömästi sodan eskaloitumisen jälkeen. Sota tarjoaa mielenkiintoisen tilaisuuden tutkia vastuullisuuden vaikutusta osaketuottoihin poikkeuksellisena aikana. Aikaisempien tutkimusten perusteella voidaan tehdä toisistaan poikkeavia oletuksia ESG-luokituksen vaikutuksesta osaketuottoihin. Vaikka eri tutkimukset ovat päätyneet etenkin eri ai koina erilaisiin lopputuloksiin, voidaan yleisesti päätellä, että osaketuottojen ja yritysten vastuul lisuuden välillä on yhteys. Tutkielmassa tarkastellaan eurooppalaisia osakkeita, jotka kuuluvat STOXX Euro 600 -osakeindeksiin. Siinä käsitellään aikaisempaa kirjallisuutta liittyen vastuulliseen sijoittamiseen sekä kriisien vaikutukseen osaketuottoihin. Sen lisäksi tutkielmassa on empiirinen osuus, jossa aihetta tutkitaan tilastotieteen menetelmin. Empiirisessä osiossa käytetään erilaisia OLS-regressioita, joilla pyritään selvittämään ESG-luokituksen vaikutusta osaketuottoihin Venäjän ja Ukrainan välisen sodan eskaloitumisen yhteydessä. Tulosten perusteella ESG-luokituksen ja osaketuottojen välillä ei havaita tilastollisesti merkittävää yhteyttä, kun ESG-luokitusta tarkastellaan kokonaisuutena. Sen sijaan, kun yritysvastuullisuuden E, S ja G osa-alueita tutkitaan erikseen, voidaan havaita lievä vaikutus sosiaalisen, ympäristöön ja hallintoon liittyvän vastuullisuuden ja osaketuottojen välillä. Sosiaalisella vastuullisuudella ja ympäristövastuullisuudella on positiivinen korrelaatio osaketuottoihin, kun taas hallintoon liittyvällä vastuullisuudella korrelaatio osaketuottoihin on negatiivinen. Tutkimuksessa tarkastellaan sivujuonteena myös NATO-jäsenyyden vaikutusta osaketuottoihin sodan eskaloituessa. Tulosten perusteella osaketuottoihin ei merkittävästi vaikuttanut se, kuuluiko yrityksen kotimaa sotilasliittoon vai ei.
Keywords: corporate responsibility; investments; finance; Russian invasion of Ukraine 2022; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance